Rest Redistribution Does Not Alter Hormone Responses in Resistance-Trained Women. Issue 7 (July 2020) - Merrigan, Justin J.; Tufano, James J.; Fields, Jennifer B.; Oliver, Jonathan M.; Jones, Margaret T.
Abstract : Abstract: Merrigan, JJ, Tufano, JJ, Fields, JB, Oliver, JM, and Jones, MT. Rest redistribution does not alter hormone responses in resistance-trained women. J Strength Cond Res 34(7): 1867–1874, 2020—The purpose was to examine acute effects of rest redistribution (RR) on perceptual, metabolic, and hormonal responses during back squats. Twelve resistance-trained women (training age 5 ± 2 years; one repetition maximum [1-RM] per body mass, 1.6 ± 0.2) performed traditional (TS, 4 sets of 10 repetitions with 120 seconds interset rest) and RR sets (4 sets of two 5 repetition clusters with 30-second intraset rest and 90-second interset rest) in counterbalanced order, separated by 72 hours. Both conditions were performed at 70% 1RM with 360 seconds of total rest. Ratings of perceived exertion (RPE) were taken after each set. Blood was sampled at baseline, after each set, and at 5, 15, 30, and 60 minutes, as well as 24 and 48 hours after training. Alpha level was p ⩽ 0.05. The RPE progressively increased throughout both conditions ( p = 0.002) with a greater overall mean for TS (5.81 ± 0.14) than RR (4.71 ± 0.14; p = 0.003). Lactate increased above baseline and remained elevated through 15 minutes post in both conditions (4.00 ± 0.76; p = 0.001), with greater lactate levels for TS (6.33 ± 0.47) than RR (4.71 ± 0.53; p < 0.001). Total testosterone was elevated after set 2 (0.125 ± 0.02; p = 0.011), but no other time point, while free testosterone remained unchanged. Growth hormone continually rose from baseline to set 3 and returned to baseline by 60 minutes post (20.58 ± 3.19). Cortisol and creatine kinase did not change over time. No condition × time interactions existed for any hormone ( p > 0.05). Use of rest redistribution resulted in lower perceived effort and lactate responses. Yet, hormone responses during rest redistribution were no different from TS.